Thomas Kuhn tentang Perkembangan Sains dan Kritik Larry Laudan - Jena, Yeremias (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2012)
Thomas S. Kuhn envisioned the development science as occured through a scientific revolution when the scientific paradigm defended by the scientific community was no longer able to solve concrete problems. The scientists then shifted to a new paradigm that was able to solve the problem as well as promising a more stable of future research. This view has been criticized by Larry Laudan who says that paradigm shift is incompatible with the reality of the development of science itself. For Laudan, science develops through an internal evolution of science itself. The paradigm will never be abandoned altogether whenever scientists face a new scientific problem. Scientific theories will prove its compatibility and update itself through the process of scientific dialogue vertically and horizontally in the hierarchical model of epistemic justification.